Lie symmetries for analyzing interaction of a characteristic shock with a singular surface in a non‐ideal reacting gas with dust particles. (23rd October 2020) - Shah, Sarswati; Singh, Randheer
Abstract : Using the invariance group properties of the system describing one‐dimensional unsteady flow of a non‐ideal dusty reacting gas, the evolutions of characteristic shock and singular surface are investigated. The effects of non‐idealness, reaction mechanism, and dusty gas parameters on the characteristic shock and singular surface are analyzed. Further, the amplitude of reflected wave and (or) transmitted wave along with bounce in the acceleration of shock, which generated from the interaction of a characteristic shock with a singular surface, are obtained.